Speech paired vagus nerve stimulation restores neural sound processing in a rat model of autism - Williams, Brendan M.; Tamaoki, Yuko; Danaphongse, Tanya T.; Myers, Isabella K.; Kroon, Samantha L.; Solano, Maria P.; Jacob, Allan A.; Riley, Jonathan R.; Chen, Min; Hays, Seth A.; Engineer, Crystal T. (Frontiers in Neuroscience, 2025)
IntroductionPrenatal exposure to valproic acid (VPA) is a common environmental cause of autism spectrum disorder (ASD) and often leads to expressive and receptive language impairments. Similar communication difficulties among individuals with ASD are often linked to abnormal subcortical and cortical sound processing. Rodents prenatally exposed to VPA exhibit degraded cortical responses to speech and an impaired ability to behaviorally discriminate speech sounds.MethodsWe sought to determine whether sound processing could be restored with paired vagus nerve stimulation (VNS). In a first experiment, we evaluated whether sound-paired VNS would alter in vivo extracellular multi-unit responses to tones, noise burst trains, and speech sounds from the anterior auditory field. We next sought to evaluate whether improvements to neural sound processing led to improvements in sound discrimination ability. In a second experiment, rats underwent go/no-go sound discrimination testing where VNS was paired with successful trials.ResultsWe found that VPA-exposed rats had degraded spectral, temporal, and speech sound processing compared to saline-exposed control rats. VPA-exposed rats which received sound-paired VNS exhibited a partial or full restoration of processing across sound types. However, across several sound discrimination tasks, we did not observe changes in behavioral performance in response to prenatal exposure to VPA or VNS.DiscussionOur study is the first to show that speech-paired VNS leads to a generalized improvement in cortical sound processing across sound types, rescuing neural processing among VPA-exposed rats. These results provide a framework for future studies to develop VNS-based interventions for communication disorders.